MiRPursuit—a pipeline for automated analyses of small RNAs in model and nonmodel plants. Issue 15 (25th July 2017) - Chaves, Inês; Costa, Bruno Vasques; Rodrigues, Andreia S.; Bohn, Andreas; Miguel, Célia M.
Abstract : miRPursuit is a pipeline developed for running end‐to‐end analyses of high‐throughput small RNA (sRNA) sequence data in model and nonmodel plants, from raw data to identified and annotated conserved and novel sequences. It consists of a series of UNIX shell scripts, which connect open‐source sRNA analysis software. The involved parameters can be combined with convenient workflow management by users without advanced computational skills. miRPursuit presents several advantages when compared to other tools, including the possibility of processing several sRNA libraries in parallel, thus easily allowing a comparison of the differences in sRNA read accumulation among sRNA libraries. We validate miRPursuit by using datasets from a model plant and discuss its performance with the analysis of sRNAs from non‐model species. Abstract :